2019
DOI: 10.1002/pon.5142
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and clinical factors of probands impacting intrafamilial disclosure and uptake of genetic testing among families with BRCA1/2 or MMR gene mutations

Abstract: Objective Intrafamilial disclosure of hereditary cancer predisposition in BRCA1/2 and mismatch repair gene (MMR) syndromes allows appropriate prevention strategies in at‐risk relatives. We previously showed in a nationwide study that the uptake of genetic targeted testing (GTT) in these families was only 30%. We aimed to identify the clinical and psychosocial factors affecting the probands' intrafamilial disclosure and relatives' uptake of GTT in BRCA1/2 or MMR syndromes. Methods We assessed clinical variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…Gender differences in communication are not surprising given that P/LP variants in common breast cancer-associated genes are most strongly associated with female cancer risks. Despite high rates of FC, prior efforts suggest 20-40% of family members remain uninformed (Barsevick et al, 2008;Hodgson et al, 2014;MacDonald et al, 2007;Sharaf et al, 2013), with substantially lower rates of FT compared to the overall rates of FC (Alegre et al, 2019;Bednar et al, 2020;Griffin et al, 2020;Hampel, 2016;Roberts et al, 2018), which is consistent with our findings. Interestingly, younger age was significantly associated with higher FC in our study, in contrast to a prior study in which older participants were more likely to share test results (Chopra & Kelly, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gender differences in communication are not surprising given that P/LP variants in common breast cancer-associated genes are most strongly associated with female cancer risks. Despite high rates of FC, prior efforts suggest 20-40% of family members remain uninformed (Barsevick et al, 2008;Hodgson et al, 2014;MacDonald et al, 2007;Sharaf et al, 2013), with substantially lower rates of FT compared to the overall rates of FC (Alegre et al, 2019;Bednar et al, 2020;Griffin et al, 2020;Hampel, 2016;Roberts et al, 2018), which is consistent with our findings. Interestingly, younger age was significantly associated with higher FC in our study, in contrast to a prior study in which older participants were more likely to share test results (Chopra & Kelly, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…However, genetic testing rates among at-risk family members are low based primarily on reports from individuals tested at academic cancer centers (Barsevick et al, 2008;MacDonald et al, 2007;Sharaf et al, 2013). Moreover, rates of family testing (FT) are substantially lower compared to overall rates of FC (Alegre et al, 2019;Bednar et al, 2020;Griffin et al, 2020;Hampel, 2016;MacDonald et al, 2007;Petersen et al, 2018;Ricker et al, 2018;Roberts et al, 2018;Sharaf et al, 2013), with two recent studies reporting that only 30% of relatives had undergone testing, with similar FC and FT across moderate-and high-risk genes for multiple cancer types (Bednar et al, 2020;Ricker et al, 2018). Neither of these latter studies evaluated resources that were used or could be helpful in FC.…”
mentioning
confidence: 99%
“…Limited disclosure within families is a significant barrier to cascade screening contributing to low uptake of genetic testing in blood relatives. 9 Indeed, studies suggest that less than half of families fully communicate BRCA risk to at-risk relatives 10 and only about one-half of relatives have cascade screening. 11 A qualitative study of 15 BRCA+ men revealed avoidant responses following learning their genetic status.…”
Section: Introductionmentioning
confidence: 99%
“…Many counselees at high hereditary BC risk reveal unmet needs about hereditary predisposition concerns [ 17 ]. Moreover, an identified genetic predisposition to cancer is not always shared among all family members [ [18] , [19] , [20] , [21] , [22] , [23] ], and when shared, it is generally incomplete or incorrect [ 24 ]. Thus, relatives of tested women may feel insufficiently informed.…”
Section: Introductionmentioning
confidence: 99%